Meta-Analysis the Effect of Acupressure in Lowering Pain of Dysmenorrhea - Rahmawati, Anisya Fajar; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: Dysmenorrhea is the most common cause of lower abdominal pain and has a negative impact on women's quality of life resulting in activity limitations. Non-pharmacological management can be used as an intervention in the management of dysmenorrhea. Acupressure is a therapy that is given by massaging or pressing certain points. The purpose of this study was to analyze the effect of acupressure therapy on reducing dysmenorrhea pain.Subject and Method: This study was a meta-analysis with the following PICO, population: Women aged 16-30 years old with primary dysmenorrhea. Intervention: administration of Acupressure Therapy. Comparison: Acupressure therapy was not performed. Results: Decreased pain in primary dysmenorrhea. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles “Acupressure” OR “Acupressure Therapy” AND “Sanyinjiao Point (SP6)” AND “Hequ Point (LI4)” AND “Dysmenorrhea” OR “Primary Dysmenorrhea” OR “Menstrual Pain” AND “Randomized Controlled Trial”. The articles included are full-text English with a Randomized Control Trial study design from 2007 to 2022. The articles were selected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: Meta-analysis of 9 randomized controlled trial articles from Asia and Europe concluded that acupressure therapy can reduce pain in primary dysmenorrhea (SMD= -0.66; 95% CI = -0.96 to -0.36; p < 0.001).Conclusion: Acupressure therapy can affect pain reduction in women with complaints of primary dysmenorrhea.Keywords: Acupressure, pain relief, primary dysmenorrheaCorrespondence: Anisya Fajar Rahmawati. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Mobile: +6285715840985. Email: anisyafajar25@gmail.com.Indonesian Journal of Medicine (2022), 07(01): 51-60https://doi.org/10.26911/theijmed.2022.07.01.06